The significant of business strategy in improving organizational performance. Issue 1 (13th February 2017) - Yuliansyah, Yuliansyah; Gurd, Bruce; Mohamed, Nafsiah
Abstract : Purpose: This research aims to investigate the extent to which business strategy mediates the relationship between reliance on integrative strategic performance measurement (RISPM) and organisational performance. Design/methodology/approach: A self-administered survey of 157 managers in Indonesian financial institutions was used to test direct and indirect effects among the hypothesised variables. Findings: The findings indicate that business strategy has a full mediating effect on the relationship between RISPM and organisational performance. Originality/value: This study indicates that performance measurement systems should be designed in conjunction with business strategies to obtain superior performance. More specifically, in the Indonesian financial institutions, applying a differentiation strategy is found to be most effective in gaining competitive advantage and superior performance.